2018
DOI: 10.1038/s41598-017-17878-x
|View full text |Cite
|
Sign up to set email alerts
|

High content image analysis reveals function of miR-124 upstream of Vimentin in regulating motor neuron mitochondria

Abstract: microRNAs (miRNAs) are critical for neuronal function and their dysregulation is repeatedly observed in neurodegenerative diseases. Here, we implemented high content image analysis for investigating the impact of several miRNAs in mouse primary motor neurons. This survey directed our attention to the neuron-specific miR-124, which controls axonal morphology. By performing next generation sequencing analysis and molecular studies, we characterized novel roles for miR-124 in control of mitochondria localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 72 publications
(81 reference statements)
1
21
0
Order By: Relevance
“…To better understand the consequences of miR-124 differential expression in MN vitality, we next assessed changes in dendritic arborization, as well as in the expression of vimentin, a neurofilament subunit [ 37 ] and a direct target of miR-124 [ 20 ], together with the perturbation of synaptic and axonal transport dynamics. We observed that both pre-miR-124-treated WT cells and mSOD1 MNs have longer primary neurites, but reduced number of ramifications (at least p < 0.05 vs. WT MNs, Figure 3 a–c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To better understand the consequences of miR-124 differential expression in MN vitality, we next assessed changes in dendritic arborization, as well as in the expression of vimentin, a neurofilament subunit [ 37 ] and a direct target of miR-124 [ 20 ], together with the perturbation of synaptic and axonal transport dynamics. We observed that both pre-miR-124-treated WT cells and mSOD1 MNs have longer primary neurites, but reduced number of ramifications (at least p < 0.05 vs. WT MNs, Figure 3 a–c).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent paper, mutant SOD1 MNs resistant to disease development showed enhanced axonal outgrowth and dendrite branching [ 67 ], which may represent a compensatory mechanism in cytoskeletal regulation, though we only observed for the neurite length. Intriguingly, the intermediate filament vimentin that is associated to neurite outgrowth [ 20 ] and a target of miR-124 [ 20 , 38 ], showed to be decreased when miR-124 was upregulated, but normal with anti-miR-124 modulation. Other factors accounting for reduced branching by miR-124 upregulation may derive from miR-146a downregulation and its known influence on the cytoskeleton actin through ROCK1 [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As latent variable models and network models are mathematically equivalent, examining the eigenvalues of components present in data using exploratory factor analysis is one way to identify how many communities might be present and the factor loadings indicate which nodes belong to which community. More sophisticated approaches include the spinglass algorithim (although this is limited by the fact that it often produces different results every time you run it, and it only allows nodes to be part of one community, whereas nodes may be better described as belonging to several communities at the same time), the walktrap algorithim (which provides more consistent results if you repeat it, but which also only allows nodes to be part of one community), and the Clique Percolation Method (CPM), which allows nodes to belong to more than one community (see Blanken et al., 2018 ).…”
Section: Centralitymentioning
confidence: 99%
“…Conversely, miR-338 has a documented function in regulating oxidative phosphorylation, as well as the expression of mitochondrial proteins such as cytochrome C (Aschrafi et al, 2008 , 2012 ). Recently, miR-124 has been shown to regulate mitochondrial activity and localization in MNs (Yardeni et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%